Faktor Yang Berhubungan dengan Pemberian Asi Eksklusif Pada Bayi - St. Aminah Ali; Baso Witman Adiaksa (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Breast milk is breast milk, one of the foods that cover all elements of the baby's physical, psychological, social, and spiritual needs at the beginning of the baby's life. The study aims to determine the factors associated with exclusive breastfeeding. This type of quantitative research uses analytical surveys with cross-sectional methods. The sample size in this study was 42 respondents who fit the inclusion and exclusion criteria. The results showed that there is a relationship between knowledge and exclusive breastfeeding with a value of p = 0.016, there is a relationship between education and exclusive breastfeeding with a value of p = 0.030, there is a relationship between work and exclusive breastfeeding with a value of p = 0.000 there is a relationship between motivation and exclusive breastfeeding with a value of p = 0.032 this shows that the value of p < α = 0.05. It can be concluded that there is a relationship between knowledge, education, work, and motivation with exclusive breastfeeding. Suggestions for mothers who are breastfeeding can increase awareness to provide exclusive breastfeeding to their babies considering the role and function of breast milk from various aspects, such as aspects of maternal immunity and health, and working mothers are expected to pay more attention to exclusive breastfeeding to their babies, this is so that babies can meet the nutritional needs and growth of infant development Mothers with higher and low education must continue to breastfeed their babies and stay motivated to find out the nutritional needs of infants.